Gamification in deaf students social behavior learning to implement SDGs: A literature review - Sartinah, Endang Pudjiastuti; Widajati, Wiwik; Budiati, Eryana Fatimasari Retno; Rahmatin, Faizur; Jehyeh, Nureeman (Edelweiss Applied Science and Technology, 2025)
The aim of this study is to investigate the application of gamification in learning as an innovation to support digital learning programs in order to motivate social behavior skills among deaf students that can affect social interaction, empathy, and cooperation. This study’s purpose is to review the literature systematically to examine the challenges faced in social behavior learning applied to deaf students and the practice of gamification in supporting social behavior learning for deaf students to promote SDG implementation. The search results were obtained using the keywords “gamification,” “deaf,” “social behavior,” and “SDGs” from literature published between 2016 and 2025. A total of 647 relevant publications from Scopus and Google Scholar were collected and processed using the PRISMA method. The analysis focused on gamification trends that have been proven to positively impact learning and the extent to which gamification supports social behavior learning for deaf students. The research underscores the importance of the ongoing contribution of gamification in the social behavior learning of deaf students, providing insights into the challenges faced in this area and the ways gamification is applied in supporting social behavior development among deaf students. These implications offer practical guidance for schools, educational technology developers, and policymakers to improve the learning system. This research contributes by providing a current synthesis of studies on how educators can effectively adapt gamification strategies to encourage social behavior among deaf students, aligning with SDG 4 objectives to support inclusive quality education.